PERANAN RUSLI ZAINAL DALAM BIDANG PEMBANGUNAN INFRASTRUKTUR DI PROVINSI RIAU TAHUN 2008-2013 - Shalehatul Mawaddah; Isjoni '; Asril ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Governor Rusli Zainal is in Riau Province in 2003-2013. He has a modest family background which makes it has passed through the career of the world politics. In its role as Governor during 2nd period, he strongly emphasized the development of infrastructure in the province of Riau related to : street, and decent housing huni) development in this period is also seen with his success in the infrastructure development of sports venues in the success of PON (national games)in Riau in 2012Keywords: Position, Government, Rusli Zainal, Development, Infrastructure, Riau